Evaluation on Recording and Reporting System of Maternal Child Health in SIKDA (Regional Health Information System) of Public Health Affair Surakarta - Nopita Cahyaningrum; Farid agushybana; Atik Mawarni (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2017)
Regional Health Information System (RHIS) is an integrated Health Information System which effectively functions as data communication in a region. This system has been used since 2012. However, it has not shown best performance. Puskesmas (Community Health Centers) send their regular reports in the form of soft copy or hard copy. However, DKK has not verified the reports on the maternal child health regularly. Moreover, they retype the report to be sent to the Ministry of Health. It results in possibility of errors in its accuracy and validity. Thus, it requires further evaluation to improve the implementation of RHIS especially in recording and reporting maternal child health to the Ministry of Health. The objective of this research is to analyze the maternal child health data recording and reporting system in RHIS Surakarta.This is a qualitative research. Data were collected by deep interview and direct observation on the implementation of the RHIS. Object of this research is the recording and reporting system of Maternal Child Health in the RHIS DKK Surakarta. The main informant is the head and the staffs of SIMKES, midwifes coordinators of SIK in 6 Community Health Centers.The results of this study propose that improvement on human resources competences should be done regularly. The data of maternal child health are taken from community health centers. That is why, there should be proper policy on the reporting the data of maternal child health. The report sent should be filed in soft copy and hard copy. Nevertheless, the available data have been processed by community health centers and are accessible for public needs.This study proposes that the recording and reporting system of maternal child health data should be developed by improving the competences of human resources, decreeing operational policy, and providing standard operating procedure.